Partisipasi Masyarakat dalam Pengelolaan Taman Nasional dengan Pola Kemitraan di Kepulauan Togean - Muh Nur Sangadji; Sumardjo Sumardjo; Pang S Asngari; Soenarmo H Soewito (Jurnal Penyuluhan, 2011)
The aim of this research are: (1) to analyze the level of community participation on management of  Togean Island National Park. (2) to analyze the factors that influence the community participation. (3) to analyze the correlation of the factors that influence the community participation, and (4) to formulate a strategy of extension to increase the effective of community participation on management of Togean Island National Park. The research was conducted in Togean Island National Park in Central Sulawesi on August to Septembre 2008 and March to April 2009. Five variables are used to measure the community participation by using Structural Equation Model (SEM) and LISEREL 8.30. Those variables are internal individu, extension process, exsternal factor, community capacity and  community participation. The result of research shown that participation of community is on the low level. Extension procces and external factor have a significant effect on community capacity. Internal characteristic and community capacity have a significant effect on community participation The independent variables such as internal characteristic, extension process and external factor have significant correlation. The strategy that can be used to increase the community participation is to improve the process of extension by giving the opportunity to community for involving on management of Togean Island National Park. This strategy should be supported by government policy to apply consistently, the partnership approach on management of national park in the local level. Keywords: community participaton, capacity, national park and extension process.